Problematika Naskh dalam Diskursus Kajian Hadis - Syaifullah, H (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2012)
In a certain problem was also still found various editorial hadith that seem contradiction between which one hadith the and with the other one hadith from this point was born the discussion of naskh in the hadith. This paper finds thas scholars divided in two on responding the naskh, namely (1) scholars who accept the existence of naskh al-hadîth and (2) scholars who rejet the naskh al-hadîth. Naskh does not reduce the perfection of revelation because in the naskh there is no purpose to measure the level of adherence to Allah and as a form of God compassion in human. More over naskh can be happen based in the indicators that all downstream to revelation